Kearifan Lokal Dalam Pengelolaan Dana Desa - Permata, Rizcha Ega; Hapsari, Aprina Nugrahesthy Sulistya (AFRE (Accounting and Financial Review), 2020)
The pouring of large and increasing annual village funds ia apparently not in line with good village financial management. Evidenced by the discovery of misappropriation of village funds that occur with a lot of fund misuse is quite large. This studi aims to lookÂ  at the role of local wisdom to reduce the risk of corruption/corruption at each stage of village fund management in Lerep Village, Ungaran Barat, Semarang Regency, Central Java. The research is a qualitative descriptive study with a phenomenological approach. The data source in this study is primary data obtained through in-depth interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The result and discussion in this research show that there is no potential for corruption in the village fund management cycle because traditional values are a form of local wisdom in Lerep Village, where these positive values can reduce the risk of corruption. The local wisdom values in Lerep Village are derived from the traditions that are routinely carried out in Lerep Village namely the tradition of iriban, merti bumi/kadeso desa, and sadranan.Â DOI: http://doi.org/10.26905/afr.v31.4294Â